Lao PDR and ADB celebrating 50 years of partnership. (Metro Manila, Philippines Asian Development Bank, 2017)
This commemorative publication presents the highlights of the development partnership between the Lao Peoples Democratic Republic and ADB over the past 50 years.
Keywords: Public administration -- Lao People Democratic Republic; Electronic books